A comunicação como estratégia de gestão das instituições públicas de ensino superior. Estudo de caso: Universidade Federal do Ceará - Lopes, Francisco Wagner de Oliveira (2009)
This work is a study on how the external communication is done by public universities, particularly by the Federal University of Ceará (UFC). In the first three chapters, a bibliographical study is carried out on how the image of the institutions is formed and kept and also some of the main theories of communication and their effects on the public opinion are reviewed. Afterwards, the communication tools and vehicles used by the UFC are analyzed as well as the consequences of this kind of communication related to the image and perception people have concerning the University. The universe researched was made up of students who entered the institution in the second semester of 2008. Theoretically, within just a month of classes those students would be less influenced by the contact with the institution and would have a closer image to the image kept by the external public. The courses of Social Communication, Administration, Nursing, Dentistry, Biological Sciences and Architecture and Urbanization were raffled and researched randomly. The results point to a strong image of good quality regarding the educational level at the UFC, however, with the main components of that education standard such as facilities, laboratories, didactic resources and professors’ motivation, contradictorily, with not very favorable images compared to the universe researched. Other issues, however, such as the way the media covers the events at the UFC and its little presence in the vehicles of mass communication may suggest explanations to the fact. The final idea is that this research can become an important indicator for other works that may be done on the theme.